Utilization of the Ruang Guru LMS as a Training Platform for Coding and Artificial Intelligence: An Analysis of Ease of Use, Usefulness, and Teacher Readiness in North Sulawesi - Rompas, Parabelem Tinno Dolf; Batmetan, Johan R; Rorimpandey, Gladly Caren; Rompas, Billy; Lumenta, Harfey (International Journal of Information Technology and Education, 2025)
As education is rapidly changing with technology, training teachers digitally has been established as a key ingredient to their lifelong learning. The application of Ruang Guru Learning Management System (LMS) is a medium for training school teachers such as senior high vocational schools to code and artificial intelligence (AI) in all districts and municipalities in North Sulawesi. The purpose of this study is to investigate the levels of perceived ease of use, perceived usefulness, digital self-efficacy and teacher readiness in participating LMS-based training. We used a quantitative description method in which we surveyed teachers who attended the coding and AI training through Ruang Guru LMS. Four-point Likert-scale questions were used to measure four constructs: ease of use, usefulness, digital self-efficacy and readiness for digital training. Descriptive statistics were used in the analysis of data. Based on the result, teachers considered that Ruang Guru LMS was easy to use and they felt it assisted them in increasing their technological skills. Their digital self-efficacy scores were between good and very good, signifying a high level of readiness for digital training. The study also signifies a need to enhance teachers’ digital skills, school infrastructure and LMS functionalities so as to ensure meaningful and sustainable digital training program.